Pulmonary placental transmogrification associated with adenocarcinoma of the lung: a case report with a comprehensive review of the literature - Ameer Hamza; Sidrah Khawar; Muhammad S. Khurram; Ahmed Alrajjal; Warda Ibrar; Sajad Salehi; Hong Qu (University of São Paulo, 2017)
Pulmonary placental transmogrification (PT) is a rare entity with less than 40 cases reported in the literature. Most reported cases are associated with either bullous emphysema or with pulmonary fibrochondromatous hamartomas. We present only the second case of PT associated with adenocarcinoma of the lung. A 67-year-old female with multiple chronic medical ailments presented with shortness of breath and was found to have a 6-cm mass in the upper lobe of her right lung. A computed tomography (CT) guided core biopsy was performed that showed a well-differentiated adenocarcinoma. Interestingly the normal lung tissue showed placental villous architecture. A unique feature of our case is that the diagnosis was made on a needle core biopsy, unlike all the other cases in the literature. We also provide a comprehensive review of this rare entity